Mendorong Gen Z : Digitalisasi Untuk Kemajuan UMKM - Desembrianti, Vebyana; Kurniawati, Endah (Gorontalo State University, 2025)
This study aims to identify the various factors that influence Generation Z's participation in developing MSMEs in Kediri District through digitalization, as well as the challenges faced in implementing digitalization.This study uses a descriptive qualitative approach method to describe the role of Generation Z in the development of Micro, Small, and Medium Enterprises (MSMEs), especially in the Kediri region. Generation Z, which is known for its high technological adaptability, has great potential in driving the digitalization of MSMEs. The results show that the involvement of Generation Z in digital marketing strategies, the use of social media, and product innovation is crucial to improving the competitiveness of MSMEs. This research provides a clear picture of the need to empower Generation Z to contribute significantly to the advancement of MSMEs in Kediri, and provides recommendations for stakeholders to create an ecosystem that supports collaboration between the younger generation and MSME players.